Structural brain network development in children following prenatal methamphetamine exposure. Issue 11 (25th January 2020) - Roos, Annerine; Fouche, Jean‐Paul; du Toit, Stefani; du Plessis, Stefan; Stein, Dan J; Donald, Kirsten A
Abstract: Brain imaging studies in children with prenatal methamphetamine exposure (PME) suggest structural and functional alterations of striatal, frontal, parietal, and limbic regions. However, no longitudinal studies have investigated changes in structural connectivity during the first 2 years of formal schooling. The aim of this study was to explore the effects of PME on structural connectivity of brain networks in children over the critical first 2 years of formal schooling when foundational learning takes place. Networks are expected to gradually increase in global connectedness while segregating into defined systems. Graph theoretical analysis was used to investigate changes in structural connectivity at age 6 and 8 years in children with and without PME. While healthy control children showed increased connectivity in frontal and limbic hubs over time, children with PME showed increased connectivity in the superior parietal cortex and striatum in their global network. Furthermore, compared to control children, those with PME were characterized by less change in segregation of structural networks over time. These findings are consistent with previous work on regions implicated in children with PME, but they additionally demonstrate alterations in structural connectivity between regions that underlie primary cognitive, behavioral, and emotional development. Understanding patterns of network development during critical periods in at‐risk children may inform strategies for supporting this group of children in these developmental tasks important for lifelong brain health and development. Abstract : Prenatal methamphetamine exposure (PME) may alter brain structure of children, but no longitudinal studies have investigated structural connectivity during the formative school years. Graph theoretical analysis was used to investigate changes in structural connectivity at age 6 and 8 years in children with and without PME. While controls showed increased connectivity in frontal and limbic hubs (i.e., regions directing brain function) over time, children with PME showed increased connectivity in the superior parietal cortex and striatum. Those with PME also had less change in segregation of structural networks over time. These findings are consistent with previous work on regions implicated in children with PME, but they additionally demonstrate alterations in structural connectivity between regions that underlie primary cognitive, behavioral, and emotional development. Understanding patterns of network development during critical periods in at‐risk children may inform supportive strategies in these developmental tasks important for lifelong brain health and development.